Philosophy and Sociology of Education in key of Recognition - Gómez Navarro, Ángel Guillermo (2018)
This essay reflects on the educational demands of the construction of identities and the recognition of cultural differences in our democratic society. To this end,the articulation of the competences underlying the two models that coexist within our educational institutions is subjected to a critical review and a position is taken in favor of an educational model that includes the humanities, taking as theoretical referent the philosophical ideas of Charles Taylor.